Influencing factor analysis based on electrical–thermal-pyrolytic simulation of carbon fiber composites lightning damage. (15th April 2016) - Dong, Qi; Guo, Yunli; Chen, Jingliang; Yao, Xueling; Yi, Xiaosu; Ping, Lu; Jia, Yuxi
Abstract: The damage of carbon fiber reinforced polymer (CFRP) laminated composites under lightning strike is analyzed by coupled electrical–thermal-pyrolytic models, which is implemented by the ABAQUS/Standard finite element code coupled with user-defined subroutines USDFLD and HEATVAL. To clarify the effects of the lightning current waveform parameters and the thermal/electrical properties of CFRPs, the damages of CFRP laminated specimens under diverse lightning current waveforms are experimentally and numerically analyzed. The results reveal that the damage volume shows a strong logarithmic relationship with the action integral, and that the damage is strongly governed by the electrical properties of CFRPs, though thermal conductivity variation barely affects the damage volume.